HAFNIUM ABUNDANCES IN FGK DWARF OF GALACTIC DISK - Gorbaneva, T. I.; Mishenina, T. V. (Одеські астрономічні публікації, 2018)
In this work we present new observational data for hafnium (72). Hf is an important element that is between the lightest rare-earth elements (e.g., La, Z = 57) with elements of the third r-process peak (Os, Ir, Pt, Z =76-78). Hafnium is the heaviest (Z = 72) stable element represented by low-excitation ( < 1:5 eV) ionized lines in the spectra of the cool stars (Lawler et al. 2007). This element is important as a stable reference element for nucleocosmochronometry, and also to study of the sources of its production and enrichment with n (neutron)-capture elements of Galactic disc. We provide the analysis of the spectra of 126 FGK dwarfs in metallicity range from −1.0 < [Fe/H] < +0.3 that were taken from our starting sample of 276 stars (Mishenina et al. 2013). The observed stars belong to the substructures of the Galaxy disc. The observations were conducted using the1.93 mtelescope at Observatoire de Haute-Provence (OHP, France) equipped with the echelle type spectrographs ELODIE and SOPHIE. The results are based on analyses of spectra that have a typical S/N ~ 100-300 and a resolution of 42 000 (ELODIE) and 75 000(SOPHIE). The hafnium abundance was derived by comparing the observed and synthetic spectra in the region of two Hf II line (λ4080.437 Å and λ4093.155 Å), making use of the LTE approximation. The obtained hafnium abundance decrease with increasing metallicity in both discs, and have a big scatter at all metallicities. The dependence of our Hf abundance on metallicity and their comparison with those of other authors is presented. It corresponds to typical behavior of the elements behind the iron peak, the elements formed in the processes of neutron capture. The sources of the Hf enrichment of Galactic disc are considered.